MENINGKATAN HASIL BELAJAR MENGGUNAKAN MODEL ROLE PLAYING PADA MATERI SBDP SISWA KELAS IV SDN 01 BENGKAYANG - Yuli; Margaretha Lidya Sumarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to improve the learning outcomes of Grade IVstudents at SDN 01 Bengkayang in the subject of Arts, Culture, and Crafts(SBDP) through the implementation of the role-playing learning model.The low learning outcomes of students are thought to be caused by a lackof active student involvement in the learning process and teachingmethods that tend to be monotonous. This research employs a classroomaction research (CAR) method conducted in two cycles. Each cycleincludes planning, action implementation, observation, and reflection. Thesubjects of this research were 33 Grade IV students of SDN 01Bengkayang in the academic year 2024/2025. Student learning outcomedata were collected through formative tests at the end of each cycle.Observational data on student and teacher activities during the learningprocess were also collected to support the analysis. The research resultsindicate a significant improvement in student learning outcomes after theimplementation of the role-playing model. In the first cycle, the averagestudent learning outcome was 51.21%, and it increased to 81.15% in thesecond cycle. This increase demonstrates that the role-playing model iseffective in enhancing students' understanding and mastery of SBDPmaterial, as it provides opportunities for students to learn actively,creatively, and enjoyably through direct role-playing experiences. Thisresearch recommends the application of the role-playing model as aninnovative and effective learning alternative for improving student learningoutcomes in the subject of SBDP at the elementary school level.